2021
DOI: 10.3389/fimmu.2021.639965
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Determinants of Differential Tuberculosis Risk in Pre-Adolescent Children and Young Adults

Abstract: The risk of progression from Mycobacterium tuberculosis (M.tb) infection to active tuberculosis (TB) disease varies markedly with age. TB disease is significantly less likely in pre-adolescent children above 4 years of age than in very young children or post-pubescent adolescents and young adults. We hypothesized that pro-inflammatory responses to M.tb in pre-adolescent children are either less pronounced or more regulated, than in young adults. Inflammatory and antimicrobial mediators, measured by microfluidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Quality control (including reproducibility against an internal positive control sample) and analysis of gene expression Ct data was performed as previously described ( 26 ) in R version 4.0.3. Delta Ct values were computed for each transcript relative to the mean of three reference transcripts ( ACTR3 , CDC42 and USF2 selected as previously described ( 27 )).…”
Section: Methodsmentioning
confidence: 99%
“…Quality control (including reproducibility against an internal positive control sample) and analysis of gene expression Ct data was performed as previously described ( 26 ) in R version 4.0.3. Delta Ct values were computed for each transcript relative to the mean of three reference transcripts ( ACTR3 , CDC42 and USF2 selected as previously described ( 27 )).…”
Section: Methodsmentioning
confidence: 99%
“…Cohort studies from the mid-20th century also demonstrated that this risk was highest for adolescent girls around the time of menarche [17,18]. The reasons underlying this increased risk of progression remain unclear, but likely stem from puberty-related changes in the immune response to M. tuberculosis [19,20].…”
Section: Rise In Tb Infection and Diseasementioning
confidence: 99%
“…The risk of progression from Mtb infection to disease is substantially lower in pre-adolescent children above 4 years of age than in postpubescent adolescents and young adults. 123 Blood gene expression profile analysis revealed that pre-adolescent children had lower levels of myeloid-associated pro-inflammatory mediators than young adults. When compared with young adults, pre-adolescent children had higher levels of IFN-stimulated genes IFNAR2, MX2, OAS1, and STAT2, as well as B cells and M2 macrophages than adults.…”
Section: Transcriptomic Profiles In Children Vs Adolescents Vs Adultsmentioning
confidence: 99%